Torvalds on Linux. - Phibbs, Mark (Far Eastern Economic Review, 2000)
Part of a special section on the battle between Microsoft Windows and Linux for control of the Chinese computer operating system market. An interview with Linus Torvalds, developer of the Linux computer operating system. Topics discussed include the position of Linux in Asia; the use of Linux as a tool to spur software development in China; and the future of Linux.